'Janet vs Freud' on Traumatization: A Critique of the Theory of Structural Dissociation from an Object Relations Perspective. (November 2016) - Lesley, Joan; Varvin, Sverre
Abstract : It is still 'Janet vs Freud'. We present 'The theory of structural dissociation' and the three‐phase treatment programme that provides the basis for treatment of traumatized patients in many services in Europe, exploring its shortcomings. With roots in Janet's work it displays a behaviouristic, systemic view of the human being that allows for an understanding of traumatic experience as preventing natural development of the personality towards an integrated unit, or disrupting integration, causing splits along fault lines between major personality systems. Traumatization, structural dissociation, produces patients with multiple inner parts, each with a subjective first person perspective of experience not (necessarily) shared with other parts. With our roots in Freud, from an object relations perspective, we illustrate, through clinical example with two traumatized female patients, how (1) the transference and countertransference provides a unique, alternative understanding of the traumatized patient determining the direction of the therapeutic process, thus making a phase‐orientated therapy moot; (2) the patient's functioning prior to traumatization influences the actual traumatic experience, reactions to it and the treatment process; and (3) a patient's attachment needs and way of handling these, brings the traumatic experience into the treatment room from the first contact, providing a core process in the transference and countertransference throughout the therapy.